Recurrent Pregnancy Loss: A Tragic Reproductive Failure - Begum, Mst Rashida; Ehsan, Mariya; Begum, Mst Sahina; Baby, Hosne Ara; Siddiqui, Maruf; Jesmin, Suha (Anwer Khan Modern Medical College Journal, 2011)
Three or more consecutive pregnancy losses are considered as recurrent pregnancy loss (RPL). About 1% of all pregnant women face this distressing problem and o.5% to 5% of spontaneous abortions are recurrent. Genetic, environmental, anatomic, hormonal, infectious and immunological factors are associated with RPL. Sometimes several factors might simultaneously be responsible for RPL. So diagnostic work up is to be extended. Life style changes, hormonal supplementation, anticoagulant and immunotherapy and surgical correction of certain uterine anatomic defects might help the couple to be parent. Genetic problem can be overcome by pre-implantation genetic diagnosis (PGD) and transferring good healthy embryos. Key Words: Recurrent Pregnancy Loss (RPL); Pre Implantation Genetic Diagnosis (PGD) DOI: http://dx.doi.org/10.3329/akmmcj.v2i2.8170 AKMMC J 2011; 2(2): 29-35